Delayed output feedback based leader–follower and leaderless consensus control of uncertain multiagent systems - Soni S.K.; Xiong X.; Sachan A.; Kamal S.; Ghosh S. (My University, 2025)
This paper proposes a distributed artificially delayed output feedback-based leader–follower and leaderless consensus control for the uncertain general linear multiagent systems (MASs) with an arbitrary relative degree. Based on the measured relative output and their delayed information with respect to neighbours, two distributed controllers are designed, which relaxes the requirement of all relative states information of agents. Through the Lyapunov–Krasovskii functional, linear matrix inequalities (LMIs) are formulated, and these LMIs are feasible for arbitrary small delays selected by the user. Delay-dependent sufficient conditions are provided to guarantee the asymptotic convergence of nominal error systems and ultimately uniform boundedness in the case of a perturbed error system, using the input to state stability (ISS) theory. Finally, the efficacy of the proposed method is illustrated through numerical examples. © 2021 The Authors. IET Control Theory & Applications published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology